Natureza, condições de vida e organização no assentamento Coqueirinho - Fortim/CE - Borges, Maria Cristiane de Jesus (2013)
The present paper is a study aiming at explaining and understanding the organisation of the Coqueirinho Settlement territory, located in the town of Fortim, in the State of Ceará. The families that have been striving to remain on the land stand out by showing a model of social organisation that develops projects with a view to the economic and social sustainability of the locality. It is very important to understand the dynamics of use and occupation of the land in order to promote the conservation of natural resources and the quality of the social, economic and environmental life of the Settlement. The methodology of this research is based on an integrated approach, with the help of a bibliographical survey, as well as a case-study of a quantitative/qualitative nature through the ADSA – Disgnostic and Analisis of Agraria Systems, with the objective of: assessing the economic and socio-environmental reality of the farmers; identifying and characterising the main production systems adopted through the application of a multi-temporal analysis of the use and occupation of the land in the period comprised between 1995-2012; understanding the context in which the settlers find themselves; producing maps that show the dynamics of use and occupation of the land, as well as point out to and examine the economic, environmental and social development capabilities of the Settlement. It is important to notice that the management of the territory is carried on by four associations, a fact that clearly shows the heterogeneity of the activities undertaken by the Settlers. There is a partnership between the Municipality and the Garbage Collectors Association. It is necessary to invest in a diversified production of the farming and animal raising subsystems. It is also important to integrate the Governmental programmes with the reality of the Settlers, and to boost the communitarian tourism already existing in the Settlement, bringing the communities together so that a socio-environmental sustainability can be created in order to secure better living conditions for the local and regional populations